(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The Federal Government of Nigeria introduced the policy of amnesty to the militants in south south Nigeria as a solution to insecurity and wanton destruction of lives and properties especially on critical infrastructures of Nigerian National Petroleum Corporation. This article, however, assessed the impact of Presidential Amnesty on security challenges in Niger Delta. Utilizing Frustration Aggression theory, the paper argued that the long accumulated frustrations of the people of Delta rising from the long-time neglect and under development of the State by various regimes and administrations have led to the continuous agitations and violence in the State. The Amnesty programme was basically oriented towards enhancing the security situation in the State for the purpose of increasing crude oil production. Employing qualitative method and relying mainly on primary and secondary sources, relevant data were generated and analyzed using thematic content analyses. The study therefore contended that there was nexus between the Amnesty Programme, national security and increase in crude oil production in Nigeria. Based on these finding therefore, it is our recommendation that the federal government should urgently and comprehensively tackle the underlying economic and social problems of Delta State in particular and Niger Delta region so as to prevent a relapse into crisis.